2021
DOI: 10.24018/ejfood.2021.3.6.407
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Banana Peel Flour in Biscuit Making as Wheat Flour Substitute

Abstract: The production of biscuits utilizing ripe banana peel flour (BPF) as a wheat flour (WF) alternative is presented in this study. Locally available Sabri banana peel was dried into a cabinet dryer at 65⁰C for 8 hours. The dried peel then turned into powder and sieved. The flours used in the preparation of the biscuits were analyzed for proximate composition. BPF contained a higher amount of fat compared to WF. Five samples of biscuits S1, S2, S3, S4, and S5 substituting WF with 0, 5, 10, 20, and 30% BPF in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…However, red amaranth stems showed a slightly higher amount of ash (2.94%) and fiber (0.98%). It was reported that tender red amaranth has 92.5% moisture, 1.8% ash, 1.2% fiber, 0.9% protein and 0.1% fat [22]. Proximate compositions of red amaranth are nearer to the observation reported in previous studies [2], [23]- [25].…”
Section: A Proximate Composition Of Red Amaranthsupporting
confidence: 48%
“…However, red amaranth stems showed a slightly higher amount of ash (2.94%) and fiber (0.98%). It was reported that tender red amaranth has 92.5% moisture, 1.8% ash, 1.2% fiber, 0.9% protein and 0.1% fat [22]. Proximate compositions of red amaranth are nearer to the observation reported in previous studies [2], [23]- [25].…”
Section: A Proximate Composition Of Red Amaranthsupporting
confidence: 48%
“…The different blends were mixed with ingredient of biscuits separately and combined well to produce appropriate dough. It was cut and then cooked for 10 to 15 min at 180 to 210 °C and left to cool before being packaged in plastic bags according to [19].…”
Section: Preparation Of Biscuits Substituted With Banana Peelmentioning
confidence: 99%
“…BP flour has also been reported to contain high protein content compared to that of BPs. The reason for the same is attributed to varietal variance, analytical methodologies, agro‐ecological situations, or time gaps between harvesting and evaluation (Khatun et al, 2021). They are also reported to be abundant in minerals such as (phosphorus, iron, calcium, magnesium, and sodium) and vitamins such as (Vitamin D, ascorbic acid, and pyridoxine) (Hikal et al, 2022).…”
Section: Nutritional Composition Of Banana and Its By‐productsmentioning
confidence: 99%